Interaction between Monetary and Macroprudential Policy to Enhance Financial Stability: Evidence from Indonesia - Yulia Indrawati; Adhitya Wardhono; Hadi Paramu; M. Abd. Nasir; Nyoman Gede Krishnabudi; Ciplis Gema Qoriah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to evaluate the interaction between monetary and macroprudential policy through the function of the central bank's objectives, namely the plain vanilla taylor rule, lean against the wind taylor rule, independent macroprudential policy rule and lean against the wind taylor rule with macroprudential policy. The parameter value used was based on the previous empirical study. The numerical optimizer csminwel of Chris Sims was used to solve the quadratic linear problems. The optimum coefficient calculation applied dynare optimal simple rule routine using the application of dynare 4.5.7 and matlab software. The result shows the macroprudential instruments, known as a buffer in monetary policy, we’re able to optimally minimize the loss function of the central bank. The central bank carried out both monetary and macroprudential policy in a comprehensive way to achieve two purposes as stated in the tinbergen principle. The interest rate policy is intended for reaching inflation and output stability, while the macroprudential policy is for credit growth. Macroeconomic stability with the addition of macroprudential policy is significant. This advantage is intended to cover greater volatility both in the policy rate and the inflation rate.